2001
DOI: 10.1074/jbc.m104454200
|View full text |Cite
|
Sign up to set email alerts
|

PsbT Polypeptide Is Required for Efficient Repair of Photodamaged Photosystem II Reaction Center

Abstract: PsbT is a small chloroplast-encoded hydrophobic polypeptide associated with the photosystem II (PSII) core complex. A psbT-deficient mutant (⌬psbT) of the green alga Chlamydomonas reinhardtii grows photoautotrophically, whereas its growth is significantly impaired in strong light. To understand the photosensitivity of ⌬psbT, we have studied the effect of strong illumination on PSII activity and proteins. It is shown that the level of PSII activity and proteins is reduced in the ⌬psbT more significantly than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 34 publications
1
42
2
Order By: Relevance
“…Only under strong illumination were PSII activity and D1 levels reduced in the Chlamydomonas mutant. In contrast to the data obtained with tobacco mutants, photosensitivity and D1 degradation in the presence of CAP were apparently not changed in the Chlamydomonas mutant, suggesting that PsbTc may not be relevant for photoprotection but may be required for an efficient recovery of photodamaged PSII in the algae (Ohnishi and Takahashi, 2001). Furthermore, PsbTc appeared to be involved in the activation of forward Q A electron flow during repair of PSII from photoinhibition in C. reinhardtii (Ohnishi et al, 2007).…”
Section: Lack Of Psbtc Results In Increased D1 Degradationcontrasting
confidence: 52%
See 1 more Smart Citation
“…Only under strong illumination were PSII activity and D1 levels reduced in the Chlamydomonas mutant. In contrast to the data obtained with tobacco mutants, photosensitivity and D1 degradation in the presence of CAP were apparently not changed in the Chlamydomonas mutant, suggesting that PsbTc may not be relevant for photoprotection but may be required for an efficient recovery of photodamaged PSII in the algae (Ohnishi and Takahashi, 2001). Furthermore, PsbTc appeared to be involved in the activation of forward Q A electron flow during repair of PSII from photoinhibition in C. reinhardtii (Ohnishi et al, 2007).…”
Section: Lack Of Psbtc Results In Increased D1 Degradationcontrasting
confidence: 52%
“…Effect of PsbTc Deletion on Assembly, Stability, and Structure of PSII Studies on PsbTc deletion mutants were reported from Synechocystis 6803 (Iwai et al, 2004) and two Thermosynechococcus species (Henmi et al, 2008) representing eubacterial organisms and from Chlamydomonas reinhardtii (Monod et al, 1994;Ohnishi and Takahashi, 2001;Ohnishi et al, 2007). Data obtained with Thermosynechococcus suggested that PsbTc is involved in the assembly of dimeric PSII complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the in vivo dimerization of PSII in cyanobacteria has been questioned due to the use of detergents for solubilization and in vitro analysis of the thylakoid complexes (Takahashi et al, 2009;Watanabe et al, 2009), there is compelling evidence for dimer formation by mutant approaches. Indeed, small PSII subunits PsbM and PsbT, located in monomer-monomer interface, have been shown crucial for proper assembly and repair of PSII (Ohnishi and Takahashi, 2001;Iwai et al, 2004;Bentley et al, 2008). Since the Sll0218 protein is expressed only under low (i.e., air level) CO 2 conditions, we postulate that the assembly of PSII dimers differs depending on the presence or absence of the Sll0218 proteins (see below).…”
Section: Sll0218 Protein Resides In the Thylakoid Membrane And Stabilmentioning
confidence: 99%
“…Chloroplast protein import assays showed that, in addition, the nuclear-encoded subunits of the water-splitting complex undergo a stepwise maturation and assembly process (Hashimoto et al, 1997). Subsequent analysis of PSII mutants in Arabidopsis that missed one or more PSII subunits refined these initial models (Ohnishi and Takahashi, 2001;Suorsa et al, 2004). Following thylakoid solubilization with nonionic detergents, various partial supercomplexes have been isolated and characterized from Arabidopsis, in particular, the complexes C2S and C2M (;880 kD), C2S2 (;1040 kD), S2SM (;1100 kD), C2S2M (1250 kD), and the full supercomplex C2S2M2 (C2S2M2) (Caffarri et al, 2009).…”
Section: Introductionmentioning
confidence: 99%